Beauty and the beast [videorecording (DVD)] - Cocteau, Jean, 1889-1963; Auric, Georges, 1899-1983; Marais, Jean, 1913-1998; Day, Josette, 1914-1972; Parély, Mila, 1917-2012; Leprince de Beaumont, Jeanne-Marie, 1711-1780 (Criterion collection, 2003)
The true love of a beautiful woman restores a beast to the handsome young prince he was, before a spell was cast on him.